Exploration of Berberine Against Ulcerative Colitis via TLR4/NF-κB/HIF-1α Pathway by Bioinformatics and Experimental Validation - Li J; Dan W; Zhang C; Liu N; Wang Y; Liu J; Zhang S (Dove Medical Press, 2024)
Jilei Li,1,* Wenchao Dan,2,* Chenchen Zhang,3 Nian Liu,3 Yichong Wang,1 Jixiang Liu,3 Shengsheng Zhang1 1Digestive Disease Center, Beijing Hospital of Traditional Chinese Medicine, Capital Medical University, Beijing, 100010, People's Republic of China; 2Department of Dermatology, Beijing Hospital of Traditional Chinese Medicine, Capital Medical University, Beijing, 100010, People's Republic of China; 3Beijing University of Chinese Medicine, Beijing, 100029, People's Republic of China*These authors contributed equally to this workCorrespondence: Shengsheng Zhang, Digestive Disease Center, Beijing Hospital of Traditional Chinese Medicine, Capital Medical University, Beijing, 100010, Tel +8613801088329, Email zhangshengsheng@bjzhongyi.comPurpose: This study aimed to delineate the molecular processes underlying the therapeutic effects of berberine on UC by employing network pharmacology tactics, molecular docking, and dynamic simulations supported by empirical validations both in vivo and in vitro.Patients and Methods: We systematically screened potential targets and relevant pathways affected by berberine for UC treatment from comprehensive databases, including GeneCards, DisGeNET, and GEO. Molecular docking and simulation protocols were used to assess the interaction stability between berberine and its principal targets. The predictions were validated using both a DSS-induced UC mouse model and a lipopolysaccharide (LPS)-stimulated NCM460 cellular inflammation model.Results: Network pharmacology analysis revealed the regulatory effect of the TLR4/NF-κB/HIF-1α pathway in the ameliorative action of berberine in UC. Docking and simulation studies predicted the high-affinity interactions of berberine with pivotal targets: TLR4, NF-κB, HIF-1α, and the HIF inhibitor KC7F2. Moreover, in vivo analyses demonstrated that berberine attenuates clinical severity, as reflected by decreased disease activity index (DAI) scores, reduced weight loss, and mitigated intestinal inflammation in DSS-challenged mice. These outcomes include suppression of the proinflammatory cytokines IL-6 and TNF-α and downregulation of TLR4/NF-κB/HIF-1α mRNA and protein levels. Correspondingly, in vitro findings indicate that berberine decreases cellular inflammatory injury and suppresses TLR4/NF-κB/HIF-1α signaling, with notable effectiveness similar to that of the HIF-1α inhibitor KC7F2.Conclusion: Through network pharmacology analysis and experimental substantiation, this study confirmed that berberine enhances UC treatment outcomes by inhibiting the TLR4/NF-κB/HIF-1α axis, thereby mitigating inflammatory reactions and improving colonic pathology. Keywords: berberine, ulcerative colitis, TLR4/NF-κB/HIF-1α, network pharmacology, molecular docking, experimental validation, inhibitor